Time and Organizational Improvisation - Crossan, Mary (2019)
This paper argues that the apparent contradiction in current conceptualizations of time in organizations (e.g., Chronos vs. Kairos) is only apparent, and that a synthesis between these opposing poles is both possible and desirable. We propose improvisation (where time to plan converges with time to act) as a vehicle for articulating a dialectical view of time-based organizational phenomena, while focusing on the three major time-related problems organizations have to solve: scheduling, synchronization, and allocation. The paper discusses how improvisation helps to synthesize even time and event time in scheduling processes, internal pacing and external pacing in synchronization processes, and linear and cyclical time in allocation processes. Methodological and practical obstacles to synthesis are also discussed.